Governo móvel: percepções sobre os aplicativos digitais móveis do Estado do Paraná - Kozievitch, Kelly Renata Mariani (2021)
Mobile technologies are present in people's daily lives and have become an indispensable accessory in personal and professional routines, and also in public management, governments are structuring themselves to follow this phenomenon that aggregates information and communication in real time. The objective of this study is to verify the effects on the generation of economic and social benefits resulting from the use of mobile digital applications made available by the State of Paraná under the perception of the government and the citizen of Paraná from the perspective of the Agency Theory, considering the possible conflicting relations between the government and the population due to informational asymmetry, and the Theory of Transaction Costs, considering the possible opportunism present in the actions of economic agents. The research is justified by the possibility of empirical evidence of possible minimization of conflicts between the State and the citizen, with the use of digital technology in the provision of public services and dissemination of knowledge about public services made available in applications for use on smartphones. The research was developed through a case study, with interviews with government representatives and citizens using mobile applications. With the results of the research, it was evidenced that the availability and use of mobile applications can generate economic and social results, of different natures, for both the government and the citizen, as well as it was evidenced that the use of these applications could contributes to the minimization of conflicts resulting from informational asymmetry and the reduction of transaction costs, according to the objective and user of each application. On the other hand, there are some conflicts generated by the availability and use of applications, which could be minimized by governance actions. It is expected that the research will contribute to the discussions of the subject, promoting reflections on the theoretical approaches explored, with the purpose of adding scientific knowledge to the accounting literature related to electronic governance and mobile government. And as a suggestion for future researches, the analysis of the budgetary and financial impacts that mobile digital applications could generate on public accounts, or even the analysis of the perceptions of governments and citizens, on the perspective of other theories aligned with the study of the public area.